A new species of Trimma (Pisces; Gobiidae) from the South-West Islands of Palau, western Pacific Ocean - Winterbottom, Richard (Zootaxa, 2018)
A new species of Trimma is described from South-West Islands of Palau. Trimma hamartium n. sp. lacks scales on the cheeks and opercle, has 8–9 scales in the predorsal midline, 17–19 pectoral-fin rays with 5–10 branched rays in the middle of the fin, an unbranched 5th pelvic-fin ray that is 51–64% the length of the 4th ray, 17–19 gill rakers on the outer surface of the first gill arch, an U-shaped interorbital trench with a narrow, slit-like postorbital trench ending at the last papilla in row p, and has 6 papillae in row c beneath the eye. When freshly collected, the species is very similar in appearance to T. preclarum, with which it is syntopic at three of the more northern islands of the South-West Islands.